Efektywność transakcji hedginowych według zasad rachunkowości zabezpieczeń - Dratwińska-Kania, Beata (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
High efficiency of hedging instruments makes more accurate budgeting and using specific accounting principles for derivative instruments and hedging activities possible. Hedging strategies are the ways to increase efficiency of hedging instruments. This article presents hedging activities efficiency and evaluates it.(original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1175, s. 80-89